KNOWLEDGE OF BREASTFEEDING TECHNIQUE AMONG POSTPARTUM WOMEN - Lilis Mamuroh; Sukmawati S; Furkon Nurhakim (Ikatan Perawat Maternitas Indonesia Provinsi Jawa Barat, 2018)
Problems in breastfeeding are caused by several causes including nipples issues (flat or injury), swollen breasts, and breast inflammation. These problems may occur due to improper breastfeeding techniques. The purpose of the research was to obtain an overview of mother's knowledge about the correct technique of breastfeeding. The research method uses descriptive approach, there were 20 women involved in this study. The results showed that 5 respondents (25%) had good knowledge, 3 (15%) had moderate knowledge, 12 (60%) had insufficient knowledge. This study also examined knowledge based on age, results showed that the majority of respondents aged 20-35 years (64.28%) had a lack of knowledge. Based on the background of formal education, the study revealed that most elementary school graduates were less knowledgeable about breastfeeding techniques (70%). Knowledge about breastfeeding techniques was also lacking in prim gravida respondents (100%). It can be concluded that respondents' knowledge is still lacking in breastfeeding techniques. Increasing women’s knowledge about breastfeeding techniques is needed because a good nutrition from breast milk will improve and support baby’s health.Keywords: breastfeeding techniques, knowledge, postpartum